2006
DOI: 10.1038/sj.hdy.6800830
|View full text |Cite
|
Sign up to set email alerts
|

Finding of male-killing Spiroplasma infecting Drosophila melanogaster in Africa implies transatlantic migration of this endosymbiont

Abstract: We report the identification of male-killing Spiroplasma in a wild-caught female Drosophila melanogaster from Uganda, the first such infection to be found in this species outside of South America. Among 38 female flies collected from Namulonge, Uganda in April, 2005, one produced a total of 41 female offspring but no males. PCR testing of subsequent generations revealed that females retaining Spiroplasma infection continued to produce a large excess of female progeny, while females that had lost Spiroplasma pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 25 publications
2
67
1
3
Order By: Relevance
“…For male-killing Spiroplasma in Drosophila, experiments indicate symbiont phenotype and vertical transmission are ablated at low temperatures. Consistent with this, male-killing Spiroplasma are recorded commonly in drosophilids from tropical biomes (Williamson and Poulson, 1979;Montenegro et al, 2005Montenegro et al, , 2006Pool et al, 2006), but not in temperate species/temperate parts of species range (see Haselkorn, 2010). This is unlikely to be a study bias, as male-killing Wolbachia have been isolated from temperate flies following observation of female-biased sex ratios produced by individual females (Hurst et al, 2000;Sheeley and McAllister, 2009;Unckless and Jaenike, 2012).…”
Section: A Generalised View Of Thermal Impacts On Facultative Heritabmentioning
confidence: 51%
“…For male-killing Spiroplasma in Drosophila, experiments indicate symbiont phenotype and vertical transmission are ablated at low temperatures. Consistent with this, male-killing Spiroplasma are recorded commonly in drosophilids from tropical biomes (Williamson and Poulson, 1979;Montenegro et al, 2005Montenegro et al, , 2006Pool et al, 2006), but not in temperate species/temperate parts of species range (see Haselkorn, 2010). This is unlikely to be a study bias, as male-killing Wolbachia have been isolated from temperate flies following observation of female-biased sex ratios produced by individual females (Hurst et al, 2000;Sheeley and McAllister, 2009;Unckless and Jaenike, 2012).…”
Section: A Generalised View Of Thermal Impacts On Facultative Heritabmentioning
confidence: 51%
“…In many cases, symbionts represent an important component of 'host adaptation to environment', conferring important properties such as resistance and tolerance to natural enemies (reviewed in Haine 2008;Brownlie and Johnson, 2009). Despite being important in host adaptation, recent molecular analyses of associations between secondary symbionts and their hosts provide evidence of successful and frequent interspecific transmission of symbionts throughout evolutionary time, alongside multiple loss events (Pool et al, 2006;Haselkorn et al, 2009;Raychoudhury et al, 2009;Mouton et al, 2012). The gain of function that can occur on symbiont acquisition and the frequency with which this occurs in nature, has led to them being considered akin to plasmids in representing heritable genomic components that can be acquired by a host species and alter its biology (Jiggins and Hurst, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The malekilling bacteria, Spiroplasma, has been found in several natural populations of D. melanogaster that occur near the equator (Montenegro et al 2000;Pool et al 2006). Veneti et al (2005) showed that Spiroplasma-infected D. melanogaster males carrying a loss-of-function mutation in any one of the five core DCC components survived to the third larval instar stage, while similarly infected males that carried no DCC mutations died as embryos.…”
mentioning
confidence: 99%